Methanol Extract Inhibition’s Effectiveness of Kawista Fruit Var. Dompu on E-Coli Through in-Vitro - Ardian Ansari; Ana Andriana; Rozikin Rozikin; I Gede Angga Adnyana (Indonesian Journal of Multidisciplinary Science, 2023)
Diarrhea is an endemic disease that causes individuals to excrete feces with a liquid consistency that have frequency of three or more times a day. The disease is caused by gastrointestinal infection due to the introduction of disease agents that can be transmitted through food, water, eating utensils, hands and flies. One of the causative agents of diarrhea is Escherichia coli. The use of various types of diarrhea drugs is basically to prevent the proliferation of Escherichia coli bacteria in the gastrointestinal tract, such as the use of Kawista fruit pulp and seeds by local people as a cure for diarrhea. The purpose of this study was to test the inhibitory activity of methanol extract of Kawista fruit pulp and seeds (Limonia acidissima L. ) Dompu variant with 4 concentrations, 25%, 50%, 75% and 100% extract concentrations. Testing antibacterial activity using the agar well diffusion method, which is done by measuring the inhibition zone around the wells. The methanol extract of Kawista fruit pulp and seeds (Limonia acidissima L. ) Dompu variant was significantly able to inhibit the growth of Escherichia coli at extract concentrations of 25%, 50%, 75% and 100% with inhibition zone diameter respectively 14.5 mm, 20.5 mm, 25.25 mm and 26.75 mm. The 100% extract concentration is classified as the concentration with the highest effectiveness in inhibiting the growth of Escherichia coli bacteria. Based on the results obtained, it can be concluded that the methanol extract of Kawista fruit pulp and seeds (Limonia acidissima L)